PENGARUH MEDIA BERGAMBAR TERHADAP PENGETAHUAN DAN SIKAP PENCEGAHAN KEKERASAN SEKSUAL PADA SISWA SEKOLAH DASAR - Dimas Dewa Darma; Asmawati Asmawati; Pauzan Efendi (JURNAL PENELITIAN TERAPAN KESEHATAN, 2021)
Sexual violence that occurs can cause psychological impacts including mental trauma, shame, even suicide desire. The purpose of this study determine the effect of on Knowledge and Attitudes About Prevention of Sexual Violence in Elementary school SD Negeri 60 Kec. Singaran Pati and SD Negeri 77 Padang Serai in Bengkulu City. The research design was quasi experimental with pre-test and post-test with control group design. The total sample of 62 people consisted of 31 intervention groups and 31 control groups. The sampling technique is random sampling choise and consequtive sampling. Analysis using a t-test at α <5%. The results showed that the mean knowledge about prevention of sexual violence in the intervention group before 55.98 intervention 78.70 (p = 0.015). The mean attitude about prevention of sexual violence in the intervention group before intervention 87,31 and After picture media there was an increase in the average attitude of 88,38 (p = 0.965). There is study the method of giving able to increase knowledge about prevention of sexual violence in children but could improve children's attitudes about preventing sexual violence